Identification of a Streptococcus agalactiae protein antigen associated with bovine mastitis isolates. - Wanger, A R (1987)
Immunoblotting was used to analyze the immune response of cows to Streptococcus agalactiae. Antibody from the milk of cows immunized (via the superficial inguinal lymph node) with formalinized S. agalactiae cells or from the milk of cows with S. agalactiae mastitis reacted strongly with a group of high-molecular-weight proteinaceous antigens. The two most predominant antigenic polypeptides in this group had apparent molecular weights of 97,000 and 104,000. Because the data indicated that these two antigens, as well as several minor antigens sometimes observed in the 70- to 100-kilodalton size range, seemed to be different forms of the same protein, we refer to the entire group as Sas97/104. A monoclonal antibody that was reactive with Sas97/104 was derived and was used to purify the antigen by affinity chromatography. Whole-cell and colony blot enzyme-linked immunoassays with either the monoclonal antibody or a polyclonal serum sample raised against the affinity-purified antigen indicated that this antigen (or cross-reactive proteins with higher molecular weights) is present on the S. agalactiae strains that were freshly isolated from mastitic cows. However, the antigen was not detected in S. agalactiae of human origin, bovine strains of S. agalactiae maintained for a prolonged period in the laboratory, or other streptococci. The data are consistent with the notion that Sas97/104 is a surface antigen and does not correspond to previously described type-specific antigens of group B streptococci.